Ensino de química para alunos cegos : desafios no ensino médio - Aragão, Amanda Silva (Universidade Federal de São Carlos, 2012)
The using of models on Chemistry Teaching is tying the understanding of various subjects, namely, molecular representation, chemical functions, stoichiometry, and others, to visual signification. These skills are important for a critical and conscious formation of the student, regarding the using of chemical substances on his daily life. Therefore, it is essential to comprehend how blind students can apprehend Chemistry notions, since that they are connected to social questions in which the individuals are involved. To understand the context of participation of these students at school in Chemistry classes, were interviewed visually impaired students of two classes of the first year of High School, of a state school in a city in São Paulo state, their Chemistry teachers and the teacher of the resources room. Beyond that, to understand the dynamics of school Chemistry classes, was performed the participant observation in these classes. Through this monitoring, was possible a better contact with the visually impaired students, what became essential for the understanding of their school routine. Regarding the difficulties on Chemistry learning is possible to say that, considering the contact with the students, they are connect to the subjects that demand visual perception and spatial interpretation, like graphics. Beyond the observation, were made pedagogical evaluations about the subject Substances and Mixtures and Atomic Models, with the aim to understand how the students apprehended the concepts involved in these subjects. Based on these data, was developed a lesson plan regarding the subject of atomistic, considering the presuppositions of historical-critical pedagogy. The classes about atomic theory resulted on the preparation of a pedagogical-didactic material in order to provide means for the apprehension of Chemistry concepts by the students. The material was used in Chemistry classes, and the elaboration of concepts, from such material, was accompanied during the process of students development and learning process.
Keywords: Educação especial; Química - ensino; Deficiência visual; Formação de conceitos; Pedagogia históricocrítica; Chemistry teaching; Visual impairment; Conceptual elaboration; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL